Mechanisms of acupuncture on vascular dementia—A review of animal studies. (July 2017) - Ye, Yang; Zhu, Wen; Wang, Xue-Rui; Yang, Jing-Wen; Xiao, Ling-Yong; Liu, Yi; Zhang, Xin; Liu, Cun-Zhi
Abstract: Vascular dementia (VaD) is the second leading type of dementia after Alzheimer's disease plaguing the aging population. Acupuncture has served as alternative and complementary medicine in the world for a long time and its use for VaD is based on a large body of preclinical and clinical researches. The mechanisms that underlie the protective effects of acupuncture are slowly beginning to be understood. Acupuncture influences multiple aspects of the pathological process of VaD. It improves cognitive function through protecting cerebral neurons from oxidative stress, apoptosis, and neuroinflammation, regulating glucose metabolism and neurotransmitters. Acupuncture may also improve synaptic plasticity and blood vessel function. It is likely that no single factor can explain the protection provided by acupuncture. This review provides a comprehensive overview of established and recent findings in animal-based researches aiming to elucidate the complex mechanisms of acupuncture on VaD. Highlights: Potential mechanisms of acupuncture on vascular dementia are summarized. Baihui (GV20) and Zusanli (ST36) are the most frequently chosen acupoints in studies for treating VaD. Neuron apoptosis and neuroinflammation are attenuated by acupuncture in VaD animal models.